Attitudes Toward Long-Acting Injectable Antipsychotics among Schizophrenia Patients in Southern Thailand: A Multihospital-Based Cross- Sectional Survey - Jarurin Pitanupong; Apinan Karakate; Laddaporn Tepsuan; Grittin Sritrangnant (Siriraj Medical Journal, 2022)
Objective: To identify the attitudes toward long-acting injectable antipsychotics (LAIs) among schizophrenia atthree psychiatric outpatient clinics in Southern Thailand from February to April 2021. Materials and Methods: A study was conducted at three psychiatric outpatient clinics. All patients, who met the criteria of having schizophrenia based on ICD-10 criteria, aged 20-60 years were included. The questionnaires utilized were:1) Demographic information, 2) Profile of schizophrenia disorder, and 3) Attitude, knowledge, and satisfaction towards LAIs. All data were analyzed using descriptive statistics. Results: There were 259 participants who completed the questionnaires. From the participants, 39% had a history of being treated with LAIs. A quarter of them felt LAIs made them feel stigmatized (26.3%), that they lost autonomy (24.7%), and embarrassed (16.6%). The reasons for refusing to receive LAIs were not fear of needles or pain at the injection site (49%), but rather that LAIs had more adverse effects than oral medications (47.9%). Half of them (51.8%) knew that they must continue to use LAIs, even though their symptoms had improved as LAIs played an important role by improving their symptoms (68.8%), and preventing relapse (51.8%). They were satisfied about having been involved in the decision making of using LAIs for their treatment (63.6%), having information on the risk-benefits from LAIs provided to them (72.3%), and the cost of LAIs (75.2%). Conclusion: Before deciding to prescribe LAIs, we should ensure that all patients receive information about the risks, and benefits of LAIs, boosting acceptance for this formulation and mitigating concerns about patient autonomy reduction and stigmatization.